4
$\begingroup$

Given: $f_1 = f_2 = 1$ and for $n \in\mathbb{N}$, $f_{n+2} =f_{n+1} + f_n$.

Prove that $f_2 + f_4 + \dots + f_{2n} = f_{2n+1}- 1$.

Would you start with setting $f_2 + f_4 + \dots + f_{2n}= a_n$?

Then for the base case let $a_1=1$ LHS$=1$ and RHS$=2-1=1$ so base case holds.

Then the inductive hypothesis: Assume $f_2 + f_4 + \dots + f_{2n} = f_{2n+1}- 1$

$\textbf{NTS}$: $f_2 + f_4 + \dots + f_{2n} +f_{2n+2} = f_{2n+3}- 1$

Inductive step: By inductive hypothesis $f_2 + f_4 + \dots + f_{2n}=f_{2n+1}- 1$

So $f_{2n+1}- 1+f_{2n+1}$=$f_{2n+2}- 1$. As was to be shown.

Is this correct or did I need to show more algebra in my inductive step ?

$\endgroup$
  • $\begingroup$ In your second line, you can just add the $-1$ over to the other side. The left-hand side collapses down to $f_{2n+1}$. $\endgroup$ – JasonM Jun 17 '16 at 4:31
  • $\begingroup$ Possible duplicate of math.stackexchange.com/questions/787341/…. $\endgroup$ – lhf Jun 24 '16 at 0:57
3
$\begingroup$

Hint. The inductive step is rather $$ f_2 + f_4 + \cdots + f_{2n}+\color{red}{f_{2n+2}}=\color{red}{f_{2n+3}}- 1, $$ then using the inductive hypothesis, we have to prove that $$ f_{2n+1}-1+\color{red}{f_{2n+2}}=\color{red}{f_{2n+3}}- 1. $$ Can you take it from here?

$\endgroup$
3
$\begingroup$

This is the core part of the inductive argument (I'll omit comments--try to piece together how each step works and comment if something is unclear): \begin{align} \sum_{i=1}^{k+1}f_{2i}&=\sum_{i=1}^kf_{2i}+f_{2k+2}\\[1em] &= (f_{2k+1}-1)+f_{2k+2}\\[1em] &= (f_{2k+2}+f_{2k+1})-1\\[1em] &= f_{2k+3}-1\\[1em] &= f_{2(k+1)+1}-1. \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.